KECERNAAN PROTEIN DAN RETENSI NITROGEN PADA DOMBA YANG DIBERI SILASE PAKAN KOMPLIT BERBAHAN ECENG GONDOK DENGAN STARTER Lactobacillus plantarum Protein Digestibilty and Nitrogen Retention on Sheep Fed with Complete Feed Silage from Water Hyacinth with Starter Lactobacillus plantarum - Hanun, L. Hanun; Muktiani, A. Muktiani; Nuswantara, L. K. Nuswantara (UPPM Politekik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2018)
This study aimed to determine the use of L. plantarum starter on a complete ration silage made from water hyacinth on protein digestibility and nitrogen retention. This study use fifteen rams (12 month old with anaverage body weight of 19 ± 3.98 kg). The sheeps were randomly devided into 3 treatment and 5 replications. T1 = elephant grass and concentrate, T2 = complete feed silage contain water hyacinth without addition of L. plantarum starter. and T3 = complete feed silage contain water hyacinth addition with L. plantarum starter. Feed structured treatment isoenergy and isoprotein (PK 13 % and 65% TDN). The result showed that the nitrogen retention, protein consumption, and protein digestibility was not significantly different among treatments. Protein consumption of treatment T1, T2 and T3 was 87,97, 108,00, 94,17 g/day, protein digestibility 77,29, 75,00, 77,07g/day and nitrogen retention was 8,82;10,47; and 8,29 g. and In conclusion, Complete feed silage water hyacinth can replace the fattening rations in sheeps.Key word : silage, L. plantarum, nitrogen retention, digestibility protein, sheep.